2010
DOI: 10.1590/s1677-55382010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Hand-assisted laparoscopic radical nephrectomy in the treatment of a renal cell carcinoma with a level ii vena cava thrombus

Abstract: Excision of renal cell carcinoma (RCC) with corresponding vena cava thrombus is a technical challenge requiring open resection and vascular clamping. A 58 year old male with a right kidney tumor presented with a thrombus extending 1 cm into the vena cava. Using a hand-assisted transperitoneal approach through a 7 cm gel-port, the right kidney was dissected and the multiple vascular collaterals supplying the tumor were identified and isolated. The inferior vena cava was mobilized 4 cm cephalad and 4 cm caudal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…In 1996, McDougall et al presented the first successful LRN with level I thrombectomy (3). During the following years, many case series studies involving LRN with level I thrombectomy were reported proving that the procedure was feasible (4,5). In this procedure, the tumor thrombus was "milked back" into the renal vein so as to block the vein with vascular clips or an endoscopic stapling device (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1996, McDougall et al presented the first successful LRN with level I thrombectomy (3). During the following years, many case series studies involving LRN with level I thrombectomy were reported proving that the procedure was feasible (4,5). In this procedure, the tumor thrombus was "milked back" into the renal vein so as to block the vein with vascular clips or an endoscopic stapling device (13).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first description of laparoscopic radical nephrectomy (LRN) with level I vena cava thrombectomy in 1996 (3), several medical centers presented laparoscopic approach to deal with RCC with level I thrombus with encouraging outcomes (4,5). One case of renal tumor with IVTT extended 3cm above the renal vein (level II tumor thrombus) managed with pure LRN with tumor thrombectomy was reported in 2006 (6).…”
Section: Introductionmentioning
confidence: 99%
“…At present, open surgery is still the standard approach for RCC with IVCTT [4]. Recently, laparoscopy is increasingly being used in RCC patients with IVCTT due to the improvement of the minimally invasive techniques and the accumulation of surgical experiences, and it has been proved to be safe and effective in selected patients [5][6][7][8][9][10][11][12]. Whether open surgery or laparoscopic surgery, it is necessary to clamp the inferior vena cava (IVC) below the inferior margin of TT and above the superior margin of the TT, followed by removing of the TT.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Laparoscopy has gained only limited application for IVC tumor thrombi and only for short thrombi that could be milked out of the IVC or in conjunction with an open incision for the IVC manipulation and tumor extraction. [2345678]…”
Section: Introductionmentioning
confidence: 99%